The Impact of The Behavior of Smartphone Usage on The Consumption of Fake News by Student - Muh.Ulil S. Negara (International Journal of Informatics and Computation, 2019)
Abstract— The background of this research is the increase of the distribution of fake news in cyberspace to coincide with the 2019 general election (Pemilu) campaign in Indonesia. Undergraduate students in Indonesia, most of whom are beginner voters in the 2019 election, are one of the most important campaign targets calculated by each political party. Fake news produced massively and structurally by political parties to get support from voters can break the unity and the harmony of the nation. Students as young people whose mindsets are critical and have idealism in fighting for their ideas must be able to distinguish between true and fake news for the safety of their own insights. The research method used is a quantitative method to understand the behavior of students in using mobile phones which is the fastest media for disseminating information through the internet. Understanding these behaviors will provide an overview of the impact of the application or information channel most often opened by someone to their ability to distinguish true and fake news. This study aims to get a strategy that needs to be done to improve student behavior in using mobile phones, which will affect the quality of information obtained from the internet via mobile phones. So that young person who are productive and have the right insight are not easily provoked by fake news from the internet